2020
DOI: 10.1057/s41599-020-0509-1
|View full text |Cite
|
Sign up to set email alerts
|

Healthy publics as multi-species matters: solidarity with people’s pets in One Health promotion

Abstract: Climate change is contributing to local disasters, and pets increasingly figure in mediated views and responses. By theorizing such responses, we expand on the conceptualization of "healthy publics". In our view, healthy publics can arise from multi-species entanglements, out of which enactments of solidarity may emerge. Such enactments may encompass people with pets, as well as the pets themselves. Such enactments are selective, however, because they highlight certain lives and vulnerable situations while obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The One Health initiative establishes that the health of people, animals, and the environment are interconnected and interdependent [ 18 ]. One Health researchers have called for consideration of the human-companion animal bond as an important factor in the interconnectedness of human and animal health [ 19 , 20 ]. This concept has been extended to the “One Welfare” platform, which asserts that the welfare of animals is tied to the well-being of humans [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…The One Health initiative establishes that the health of people, animals, and the environment are interconnected and interdependent [ 18 ]. One Health researchers have called for consideration of the human-companion animal bond as an important factor in the interconnectedness of human and animal health [ 19 , 20 ]. This concept has been extended to the “One Welfare” platform, which asserts that the welfare of animals is tied to the well-being of humans [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Access to veterinary care was identified as a critical One Health problem in animal sheltering (Horecka and Neal, 2022) and researchers have reported quantitative metrics on the use of community veterinary services applying the concept One Welfare (Ly et al, 2021), One Health (Hawes et al, 2021) or through initiatives like Pets for Life (PFL, 2021) of the Humane Society of the United States (Decker-Sparks et al, 2018). Rock and Blue (2020) connected One Health to social inequity and thus expanded the concept to pet ownership and housing security. Jordan and Lem (2014) reported that a community veterinary and social services initiative that utilised a "One Health, One Welfare" model promoted empathy in veterinary students, and Panning et al (2016) suggested that this model could improve the health of vulnerable human and animal populations.…”
Section: Introductionmentioning
confidence: 99%